2010
DOI: 10.1007/s00520-010-0847-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of trismus induced by cancer therapies in head and neck cancer patients

Abstract: Newer radiation modalities may decrease the prevalence of trismus compared to conventional radiotherapy. Few studies have addressed the quality of life impact of trismus, and no studies were identified to assess the economic impact of trismus. The few preventive and management trials identified in the literature showed some promise, although larger, well-designed studies are required to appropriately assess these therapies before recommendations can be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
164
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 23 publications
2
164
0
8
Order By: Relevance
“…Our results demonstrated that patients who fed trough NTF had greater MMO restriction compared to patients who remained feeding orally. The mandibular hypomobility caused by the use of NTF accelerates the degeneration of the muscles and the temporomandibular joint caused by RT 50 . Several studies have reported the use of chewing gum for the treatment of trismus 19,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that patients who fed trough NTF had greater MMO restriction compared to patients who remained feeding orally. The mandibular hypomobility caused by the use of NTF accelerates the degeneration of the muscles and the temporomandibular joint caused by RT 50 . Several studies have reported the use of chewing gum for the treatment of trismus 19,26 .…”
Section: Discussionmentioning
confidence: 99%
“…When the temporomandibular joint and masticatory muscles are irradiated, there is a risk of developing trismus [6,7]. This risk increases in proportion to radiation dose and irradiated volume of relevant anatomical structures [2,8,9]. The reported prevalence of trismus after radiotherapy for head and neck cancer ranges from 25% to 42% [2,9].…”
mentioning
confidence: 99%
“…Many patients with head and neck cancer suffer from trismus (a mouth opening of 35 millimeters (mm) or less), especially after radiotherapy [1,2]. Fibrosis is considered one of the biological mechanisms leading to late radiation-induced side effects [3][4][5].…”
mentioning
confidence: 99%
“…5 To the best of our knowledge, our study is the first to show that TC Qigong training was able to attenuate the deterioration in mouth opening capacity among NPC survivors. The participants that did not undergo TC Qigong training demonstrated a dramatic decrease in interincisor distance over the 12-month study period (Table 3).…”
Section: Discussionmentioning
confidence: 95%
“…1 Currently, the primary medical management for NPC is radiotherapy, while chemotherapy and surgery (eg, nasopharyngectomy) are elective treatments. 2 Although previous research has shown that these aggressive treatment methods can successfully control tumors and thus increase overall survival rates, 1 survivors generally experience many associated side effects, such as neck muscle fibrosis, 3,4 trismus or restricted mouth opening, 5,6 and shoulder dysfunctions. 7 The disease can also directly cause chronic symptoms, such as pain and fatigue.…”
Section: Introductionmentioning
confidence: 99%